Application of IR-radiometric diagnostics for control of vacuum connections of electrophysical installations - Prohorenko, E.M.; Klepikov, V.F.; Lytvynenko, V.V.; Bazaleyev, N.I.; Magda, I.I.; Prohorenko, T.G.; Morozov, A.I. (Вопросы атомной науки и техники, 2018)
The methods of IR-radiometric diagnostics of vacuum systems have been worked out. Several mechanisms are proposed that change the temperature field in the defect region. Depending on the type of defect, the main types of temperature anomalies are identified. The influence on the results of thermo graphic survey of such parameters as the assembly quality of the accelerator assemblies, the state of the material, and the cleanliness of the flange surface was studied. The possibility of detecting suction in case of a breach of air tightness of ducts is shown. To detect micro leakage of vacuum connections of the accelerator flanges, an IR-radiometric control is performed. Found leaks based on the received thermograms. They are found in the region of gas throttling or areas of variation in of the coefficient of radiation. Systematization of thermo images of defects in vacuum systems has been carried out. Systematized on the basis on the types of damage.